Flow cytometry: An accurate tool for screening P2RX7 modulators. Issue 8 (18th December 2020) - Barczyk, Amélie; Bauderlique‐Le Roy, Hélène; Jouy, Nathalie; Renault, Nicolas; Hottin, Audrey; Millet, Régis; Vouret‐Craviari, Valérie; Adriouch, Sahil; Idziorek, Thierry; Dezitter, Xavier
Abstract: The P2X purinergic receptor 7 (P2RX7) is a poorly selective ATP‐gated ion channel. Although P2RX7 binds ATP with relatively low affinity, prolonged activation can lead to nonselective membrane pore formation. Indeed, brief exposure to ATP triggers a rapid Ca 2+ influx, whereas prolonged exposure to high ATP concentrations results in the passage of larger organic molecules. P2RX7 is involved in the physiopathology of a number of diseases and has notably emerged as a potential therapeutic target in inflammation, neuropathic pain, Alzheimer's disease, and cancer—prompting growing interest in the synthesis of novel P2RX7 modulators and the development of reliable, stringent screening methods. In the present study, we developed methods based on conventional flow cytometry, imaging flow cytometry and spectral flow cytometry and used them to measure P2RX7's activity upon activation by 3'‐O‐(4‐benzoyl)benzoyl ATP. We also demonstrated the use of the highly sensitive DNA‐intercalating dye TO‐PRO‐3 to determine P2RX7's large pore activity. The simultaneous quantification of calcium influx (Fluo‐3 AM), large pore opening (TO‐PRO‐3), and viability (propidium iodide) is a very efficient method for low‐ to medium‐throughput screening of P2RX7 modulators. Agonist and antagonist potencies can be accurately evaluated. Spectral cytometry notably enabled us to assay several biological activities while correcting for the intrinsic fluorescence of the screened compounds—otherwise a well‐known limitation of fluorescence‐based screening. Hence, spectral cytometry appears to be a useful, novel tool for drug candidate screening.